Derivation and Evaluation of a New Extinction Coefficient for use with the n-HUT Snow Emission Model - Maslanka, William; Sandells, Melody; Gurney, Robert; Lemmetyinen, Juha; Leppänen, Leena; Kontu, Anna; Matzl, Margret; Rutter, Nick; Watts, Tom; Kelly, Richard (IEEE Transactions on Geoscience and Remote Sensing, 2019)
In this study, snow slab data collected from the Arctic Snow Microstructure Experiment was used in conjunction with a six-directional flux coefficient model to calculate individual slab absorption and scattering coefficients. These coefficients formed the basis for a new semi-empirical extinction coefficient model, using both frequency and optical diameter as input parameters, along with the complex dielectric constant of snow. Radiometric observations, at 18.7, 21.0, and 36.5 GHz at both horizontal and vertical polarizations, and snowpit data collected as part of the Sodankylä Radiometer Experiment were used to compare and contrast the simulated brightness temperatures produced by the n-HUT snow emission model, utilizing both the original empirical model and the new semi-empirical extinction coefficient model described here. The results show that the vertical polarization RMSE and bias values decreased when using the semi-empirical extinction coefficient; however, the horizontal polarization RMSE and bias values increased on two of the lower microwave bands tested. The unbiased RMSE was shown to decrease across all frequencies and polarizations when using the semi-empirical extinction coefficient.